Designing hybrid barium tungstate on functionalized carbon black as electrode modifier for low potential detection of antihistamine drug promethazine hydrochloride. (15th June 2021) - Muthukutty, Balamurugan; Vivekanandan, Alangadu Kothandan; Chen, Shen-Ming; Sivakumar, Mani; Chen, Shih-Hsun
Abstract: Promethazine hydrochloride (PMHC) is a first-generation antihistamine drug used to treat allergic rhinitis, allergic conjunctivitis, urticaria, etc., Overdosage of PMHC affects majorly the central nervous system such as respiratory tract, dermatologic, cardiovascular and hematologic. Hence, the detection of PMHC considered being an important factor in day to day life of the human. In this work, we developed barium tungstate (BaWO4 ) unified with functionalized carbon black ( f- CB) via an eco-friendly synthesis technique to detect PMHC. As prepared BaWO4 / f- CB composite was analyzed through various spectroscopic and microscopic techniques. The electrochemical property of the as-prepared composite was investigated through electron impedance spectroscopy (EIS), and voltammetric techniques with a disposable screen-printed carbon electrode (SPCE) as a working electrode. BaWO4 / f- CB/SPCE outcomes with least charge resistance, higher anodic current, dual wider linear range, lower limit of detection (29 nM) & limit of quantification (264 nM), excellent sensitivity, and selectivity towards PMHC. Additionally, the PMHC concentration in pharmaceutical formulations (medical wastes) largely pollutes the hydric resources. Hence, the lake water was chosen to analyze the practical feasibility of a proposed sensor. The practical utility of BaWO4 / f- CB sensor fallout with good electrocatalytic activity at trace level detection of PMHC. Graphical abstract: Superlatively Intermingled BaWO4 / f -CB modified sensor for sustained and enhanced electrochemical sensing of Promethazine. Image 1 Highlights: The barium tungstate (BaWO4 ) unified with functionalized carbon black ( f -CB) via an eco-friendly synthesis method. BaWO4 / f -CB/SPCE outcomes with least charge resistance, higher anodic current. BaWO4 / f -CB sensor exhibits excellent LOD (29 nM), LOQ (264 nM), sensitivity (826 mM μA −1  cm −2 ) and selectivity towards PMHC. The practical utility of the BaWO4 / f -CB sensor exhibits a good recovery rate in lake water samples.